Macrophage‐Inducing FasL on Chondrocytes Forms Immune Privilege in Cartilage Tissue Engineering, Enhancing In Vivo Regeneration. (May 2014) - Fujihara, Yuko; Takato, Tsuyoshi; Hoshi, Kazuto
Abstract To obtain stable outcomes in regenerative medicine, controlling inflammatory reactions is a requirement. Previously, auricular chondrocytes in tissue‐engineered cartilage have been shown to express factors related to immune privilege including Fas ligand (FasL) in mice. Since elucidation of mechanism on immune privilege formed in cartilage regeneration may contribute to suppression of excessive inflammation, in this study, we investigated the function of FasL and induction of immune privilege in tissue‐engineered cartilage using a mouse subcutaneous model. When cocultured, auricular chondrocytes of FasL‐dysfunctional mice, C57BL/6JSlc‐gld/gld (gld), induced less cell death and apoptosis of macrophage‐like cells, RAW264, compared with chondrocytes of C57BL/6 mice (wild), suggesting that FasL on chondrocytes could induce the apoptosis of macrophages. Meanwhile, the viability of chondrocytes was hardly affected by cocultured RAW264, although the expression of type II collagen was decreased, indicating that macrophages could hamper the maturation of chondrocytes. Tissue‐engineered cartilage containing gld chondrocytes exhibited greater infiltration of macrophages, with less accumulation of proteoglycan than did wild constructs. Analysis of the coculture medium identified G‐CSF as an inducer of FasL on chondrocytes, and G‐CSF‐treated tissue‐engineered cartilage showed less infiltration of macrophages, with increased formation of cartilage after transplantation. The interactions between chondrocytes and macrophages may increase G‐CSF secretion in macrophages and induce FasL on chondrocytes, which in turn induce the apoptosis of macrophages and suppress tissue reactions, promoting the maturation of tissue‐engineered cartilage. These findings provide scientific insight into the mechanism of autologous chondrocyte transplantation, which could be applied as a novel strategy for cartilage tissue engineering. Stem Cells2014;32:1208–1219